2011
DOI: 10.4103/0028-3886.91354
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne or Becker muscular dystrophy: A clinical, genetic and immunohistochemical study in China

Abstract: This study may be important to enable comparisons of mutation type and the most appropriate analytical approach for samples from different geographical areas and ethnicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As previous studies have suggested, chronic persistent CK elevation indicates the possibility of neuromuscular disease (11). Wang et al (12) reported that among a group of 201 female relatives, 97 of the 98 first-degree relatives with high levels of CK were DMD or BMD carriers, while 31 of the remaining 103 subjects exhibiting normal CK levels were diagnosed as carriers. Therefore, the possibility that female relatives with normal levels of CK could be carriers cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have suggested, chronic persistent CK elevation indicates the possibility of neuromuscular disease (11). Wang et al (12) reported that among a group of 201 female relatives, 97 of the 98 first-degree relatives with high levels of CK were DMD or BMD carriers, while 31 of the remaining 103 subjects exhibiting normal CK levels were diagnosed as carriers. Therefore, the possibility that female relatives with normal levels of CK could be carriers cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of female carriers is important to avoid the birth of affected children ( 4 ). CK is currently the most common used non-invasive biomarker in detecting carriers, but since CK is not always reliable and only 45.0–76.0% of female carriers have increased levels of CK, the search for new biomarkers in detecting DMD/BMD carriers is especially important ( 5 7 , 22 ). At present, there are also some studies on miRNAs as biomarkers of DMD, but few are about DMD carriers.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that ~2.5–40.0% of female carriers will have manifestations of muscular dystrophy (MD) such as muscle weakness or heart disease later on in their life, but these people rarely show symptoms during childhood ( 2 4 ). In addition, multiple studies have shown that ~45–76% of female carriers have increased serum creatine kinase (CK) levels, while others are normal ( 5 7 ). For those asymptomatic carriers with normal CK levels, their affected male relatives are usually the first indication of their so-called “gene carrier” status ( 8 ).…”
Section: Introductionmentioning
confidence: 99%